Youth access to empowerment funds for entrepreneurship in Zambia - Simuyandi, Bertha Miyanda (Department of Social Development, 2020)
Youth unemployment in Zambia is high. According to the Zambia Country Report (2013) by the United Nations Population Fund (UNFPA), approximately 960,000 (16.7 %) of the almost 6 million youths in Zambia are unemployed. This has led to young people engaging in entrepreneurial activities as a means of survival. However, they are faced with difficulties in accessing empowerment funds for entrepreneurship. An exploratory study was conducted in the Lusaka Province of Zambia. The aim of the study was to explore successes and challenges faced by the youth in accessing empowerment funds for entrepreneurship in Zambia. Triangulation of quantitative and qualitative research methods was used for the study. Sampling was done to select the youths that would take part in the quantitative survey. Sixty youths who applied for the empowerment funds were selected to take part in the survey which was done by questionnaire. The software ‘Statistical Package for Social Sciences’ (SPSS) was used for the quantitative data analysis. A Purposive Sampling method was used because the selected youths and stakeholders were considered to be suitable to participate in the study. The sample size selected from the research population was 30. Twenty youths who applied for empowerment funds and 10 representatives of the stakeholders were interviewed. Semistructured interviews were used as data collection tools. For the qualitative data analysis, Tesch’s steps were used. The study found that several factors affect youth access to empowerment funds for entrepreneurship in Zambia. These factors could be divided into four groups: economic and financial, institutional, social and miscellaneous. The main economic and financial factors included unemployment and lack of income, lack of collateral, savings by the youth, bank charges and poor financial habits. The main institutional factors were found to be legal regulatory framework, poor policies and bureaucracy. The main social factors were lack of entrepreneurship education, skills training and non-existent youth services. Other factors were negative societal social and cultural perceptions, practices and attitudes, logistical issues and lack of information. The recommendations for access to empowerment funds for entrepreneurship by youth in Zambia can be divided into five main categories, namely alternative funding sources, communication, financial, institutional and miscellaneous. The youths should seek other sources of money, disbursing agencies should use different mediums for disseminating information about empowerment funds, the government should strengthen disbursing agencies for provision of empowerment funds equitably, and there is a need for appropriate financial practices to be adopted by the youth. The study is exploratory and identifies the factors that affect the youth’s access to empowerment funds for entrepreneurship in Zambia. Further research should be done to assess attitudes of funders towards youth entrepreneurs so as to gauge whether access to financial interventions are effective or not. Further research is also needed to understand why youth entrepreneurs tend to shun certain entrepreneurial activities such as farming.